Mapping The Physical Vulnerability Level of Residential Fires in Alalak Tengah Urban Village, North Banjarmasin Sub-district - Agus Riyanto; Deasy Arisanty; Muhammad Muhaimin; Sidharta Adyatma; Aswin Nur Saputra (GEOGRAFI, 2025)
Indonesia is an area that is vulnerable to various disasters, one of which is residential fires. Banjarmasin City has the highest population density and fire frequency in South Kalimantan. Alalak Tengah Urban Village is the urban village with the highest area of slums in North Banjarmasin Sub-district. Slums are often accompanied by a decline in the quality and facilities of settlements, making them areas that allow settlement fires to occur. Mapping vulnerability levels is necessary for disaster risk management. This research uses qualitative analysis based on Geographic Information System (GIS). The parameters used in this study are the density of residential buildings, type of residential buildings, settlement layout pattern, distance from water source location, distance from fire extinguisher location, distance from main road, and width of driveway. The research shows that the level of physical fire vulnerability in Alalak Tengah Village is divided into three levels with a low vulnerability level of 8.2 Ha, a medium vulnerability level of 11.7 Ha, and a high vulnerability level of 16.4 Ha. The high vulnerability level dominates with areas that have limited access, with dense settlements, and flammable building materials. The results of the physical vulnerability map of residential fires are reliable, with map accuracy test results ≥80%.